2011
DOI: 10.2147/ijn.s20263
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of ligustrazine ethosome patch in rats and anti-myocardial ischemia and anti-ischemic reperfusion injury effect

Abstract: The objective of this study was to investigate the pharmacokinetics of the ligustrazine ethosome patch and antimyocardial ischemia and anti-ischemic reperfusion injury effect. Male Sprague Dawley rats were divided randomly into 3 groups: Group A (intragastric ligustrazine), Group B (transdermal ligustrazine ethosome patch), and Group C (conventional transdermal ligustrazine patch). After treatment, samples of blood and of various tissues such as heart, liver, spleen, lung, kidney, brain, and muscle samples wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 6 publications
1
18
0
Order By: Relevance
“…[97][98][99] The preparation and evaluation of ethosomal patches are more complicated than for ethosomal gels, as molds are required for their preparation. Based on a literature search, only seven research articles had reported ethosomal patch formulations for several drugs, ie, testosterone, 6 artesunate and febrifugine, 27 ligustrazine, 34,118 valsartan, 37 tizanidine hydrochloride, 119 and insulin. 120 Different polymers were used to prepare the ethosomal patches, including polyvinylpyrrolidone/vinyl acetate, acrylic resin, and hydroxypropyl methylcellulose E15.…”
Section: Ethosomal Gelsmentioning
confidence: 99%
“…[97][98][99] The preparation and evaluation of ethosomal patches are more complicated than for ethosomal gels, as molds are required for their preparation. Based on a literature search, only seven research articles had reported ethosomal patch formulations for several drugs, ie, testosterone, 6 artesunate and febrifugine, 27 ligustrazine, 34,118 valsartan, 37 tizanidine hydrochloride, 119 and insulin. 120 Different polymers were used to prepare the ethosomal patches, including polyvinylpyrrolidone/vinyl acetate, acrylic resin, and hydroxypropyl methylcellulose E15.…”
Section: Ethosomal Gelsmentioning
confidence: 99%
“…Ligustrazine plays a role in expanding blood vessels, increasing both coronary and cerebral blood flow, preventing platelet aggregation, inhibiting thrombosis, and improving microcirculation [2] . It also decreases hematological indices of myocardial ischemia in rats and protects against acute myocardial ischemia and myocardial ischemia-reperfusion injury [3] . Through the study of TMP derivatives, we unexpectedly found that liguzinediol (which has been patented [4] ) has significant positive inotropic effects, which were stronger than those of TMP.…”
Section: Introductionmentioning
confidence: 98%
“…Meanwhile, we come to know that TMP also can inhibit the apoptosis of spinal cord injury cells (9) as well as can help in the production of endothelin, which can dilate vessels and increase the effect of blood supply in the ischemic area (10). It can inhibit the aggregation of platelet thus, reducing blood viscosity simultaneously improve microcirculation and regulate the expression of interleukin in order to inhibit inflammation (11). Angiogenesis might be a condition for the growth of primary and metastatic tumors.…”
Section: Introductionmentioning
confidence: 99%